Using residential histories in case-control analysis of lung cancer and mountaintop removal coal mining in Central Appalachia. (November 2020) - Christian, W.J.; Walker, C.J.; Huang, B.; Levy, J.E.; Durbin, E.; Arnold, S.
ABSTRACT: Population-based ecological and cross-sectional studies have observed high risk for several cancers in areas of Central Appalachia where mountaintop removal coal mines operate. Case-control studies could provide stronger evidence of such relationships, but misclassification of exposure is likely when based on current residence, since individuals could have inhabited several residences with varying environmental exposures over many years. To address this, we used residential histories for individuals enrolled in a previous case-control study of lung cancer to assess residential proximity to mountaintop removal coal mining over a 30-year period, using both survey data and proprietary data from LexisNexis, Inc. Supplementing the survey data with LexisNexis data improved precision and completeness of geographic coordinates. Final logistic regression models revealed higher odds of high exposure among cases. These findings suggest that living in close proximity to mountaintop removal coal mining sites could increase risk for lung cancer, after adjusting for other relevant factors.